Impacts devalue the potential of large-scale terrestrial CO2 removal through biomass plantations. (15th September 2016) - Boysen, L R; Lucht, W; Gerten, D; Heck, V
Abstract: Large-scale biomass plantations (BPs) are often considered a feasible and safe climate engineering proposal for extracting carbon from the atmosphere and, thereby, reducing global mean temperatures. However, the capacity of such terrestrial carbon dioxide removal (tCDR) strategies and their larger Earth system impacts remain to be comprehensively studied—even more so under higher carbon emissions and progressing climate change. Here, we use a spatially explicit process-based biosphere model to systematically quantify the potentials and trade-offs of a range of BP scenarios dedicated to tCDR, representing different assumptions about which areas are convertible. Based on a moderate CO2 concentration pathway resulting in a global mean warming of 2.5 °C above preindustrial level by the end of this century—similar to the Representative Concentration Pathway (RCP) 4.5—we assume tCDR to be implemented when a warming of 1.5 °C is reached in year 2038. Our results show that BPs can slow down the progression of increasing cumulative carbon in the atmosphere only sufficiently if emissions are reduced simultaneously like in the underlying RCP4.5 trajectory. The potential of tCDR to balance additional, unabated emissions leading towards a business-as-usual pathway alike RCP8.5 is therefore very limited. Furthermore, in the required large-scale applications, these plantations would induce significant trade-offs with food production and biodiversity and exert impacts on forest extent, biogeochemical cycles and biogeophysical properties.